Investigating the effect of SPRM on mechanical strength and thermal conductivity of highly porous alumina ceramics. Issue 18 (15th December 2017) - Wang, Jianzhu; Zhao, Junxue
Abstract: For recycling waste refractory materials in metallurgical industry, porous alumina ceramics were prepared via pore forming agent method from α-Al2 O3 powder and slide plate renewable material. Effects of slide plate renewable material (SPRM) on densification, mechanical strength, thermal conductivity, phase composition and microstructure of the porous alumina ceramics were investigated. The results showed that SPRM effectively affected physical and thermal properties of the porous ceramics. With the increase of SPRM, apparent porosity of the ceramic materials firstly increased and then decreased, which brought an opposite change for the bulk density and thermal conductivity values, whereas the bending strength didn't decrease obviously. The optimum sample A2 with 50 wt% SPRM introducing sintered at 1500 °C obtained the best properties. The water absorption, apparent porosity, bulk density, bending strength and thermal conductivity of the sample were 31.7%, 62.8%, 1.71 g/cm 3, 47.1 ± 3.7 MPa and 1.73 W/m K, respectively. XRD analysis indicated that a small quantity of silicon carbide and graphite in SPRM have been oxidized to SiO2 during the firing process, resulting in rising the porous microstructures. SEM micrographs illustrated that rod-like mullite grains combined with plate-like corundum grains to endow the samples with high bending strength. This study was intended to confirm the preparation of porous alumina ceramics with high porosity, good mechanical properties and low thermal conductivity by using SPRM as pore forming additive.